Smart concrete with autonomous crack repair function - Chen, Yifei (Nanyang Technological University, 2023)
Previous research has explored using Microbial Induced Carbonate Precipitation (MICP) with reactive magnesia cement (RMC) mixtures. This approach has proven effective in repairing cracks. However, it requires the activation of bacteria, which is more time-consuming than the Enzyme Induced Carbonate Precipitation (EICP) method. Additionally, the high costs and lengthy cultivation time for bacteria make MICP challenging to produce on a large scale for construction purposes. In this study, the project focuses on investigating the properties of the urease enzyme and its role in Urease Enzyme-Induced Carbonate Precipitation for concrete repair and finding the optimum ratio for the highest concrete surface healing efficiency.